Analisis Bibliometrik Tentang Qiraat Sab’ah Menggunakan VOSViewer Berbasis Data Google Scholar - Zaini Hafidh; Yayah Rahyasih; Arfan Muchammad Agfirlana (Jurnal test, 2023)
This study aims to analyze and describe the publication of scientific articles with the research theme Qiraat Sab’ah." The Qiraat Sab’ah research analysis uses the VOSViewer through a bibliometric approach. Article references are obtained from databases with publication or perishability application support. The word 'Qiraat Sab’ah' becomes a reference in the research process. Found 42 articles considered relevant to this topic. The research period used in a document indexed by Google Scholar is the last 10 years (2012–2022). The search results focus on research and analysis of terms related to Qiraat Sab’ah and other data analysis. The keywords on 'Qiraat Sabah' are associated with 5 clusters and 149 links, resulting in a total link strength of 323. The results of the analysis of the development of Qiraat Sab’ah posts over the past 10 years as a whole are still fluctuating and even tend to be less desirable; the highest number of publications in 2021 is 14 articles, and at least in 2013, there were 0 articles. The researcher examines published articles on Qiraat Sab’ah and its relation to the issues using the VOSViewer. This study may be a starting point for research related to further research on Qiraat Sab’ah and further research developments on Ulumul Qur'an in the future.